2011
DOI: 10.1007/s12262-011-0239-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Glyceryl Trinitrate Ointment Versus Surgical Management of Chronic Anal Fissure

Abstract: Chronic Anal Fissure (CAF) is common perineal condition and well-known painful entity. Standard surgical treatment even though available, may require long hospital stay and sometimes have worrying complications like anal incontinence. So non-surgical treatment, Glyceryl Trinitrate has been shown to be an effective for chronic anal fissure. It decreases anal tone and ultimately heals the anal fissure. The present study is the attempt to know the efficacy of 0.2% Glyceryl Trinitrate ointment in the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Age group in most studies were between 31 to 40 years [6][7][8][9]. Most of the patients were from younger age group in present study which might be due to changing habits of low fiber diet in young age group leading to constipation and subsequent anal fissure.…”
Section: Study Of Operated Patients Of Lateralmentioning
confidence: 72%
See 2 more Smart Citations
“…Age group in most studies were between 31 to 40 years [6][7][8][9]. Most of the patients were from younger age group in present study which might be due to changing habits of low fiber diet in young age group leading to constipation and subsequent anal fissure.…”
Section: Study Of Operated Patients Of Lateralmentioning
confidence: 72%
“…Study done by Tauro LF et al, had shown incidence of flatus incontinence of 3.3% and anal seepage of 6.6% in lateral sphincterotomy group [8]. 'Study of "tailored" lateral sphincterotomy by selecting the height of sphincter to be divided' done by David RG Littlejohn et al had shown that incidence of imperfect control of flatus of 1.4%, minor staining of 0.35 % and urgency of 0.7 %, which is less compared to our study [11].…”
Section: Study Of Operated Patients Of Lateralmentioning
confidence: 89%
See 1 more Smart Citation
“…5 Fissures often recur after medical therapy. 6 On the other hand, surgical treatment of chronic anal fissure is associated with complications such as ecchymosis, hematoma, 7 pain, postsurgical secondary infection, 8 abscess and fistula formation, 9 long hospital stay, 10 and a degree of incontinence, which has been reported to be in up to 30% of patients. 11 Nowadays, the use of nonsurgical method as the first-line treatment of chronic anal fissure is well accepted.…”
mentioning
confidence: 99%
“…Because of possibility of failure and complications after surgery, research for the nonsurgical treatment of chronic fissure continues. 10 Complementary and alternative medicine is a branch of medicine based on the holistic concept of health that can improve the quality of life along with the treatment of the ailment. 12 The philosophy behind complementary and alternative medicine is different from that of Western medicine.…”
mentioning
confidence: 99%